Exploring the Preventive Effect and Mechanism of Senile Sarcopenia Based on “Gut–Muscle Axis” - Liao, Xiaoshan; Wu, Mengting; Hao, Yuting; Deng, Hong (Frontiers in Bioengineering and Biotechnology, 2020)
Age-related sarcopenia probably leads to chronic systemic inflammation and plays a vital role in the development of the complications of the disease. Gut microbiota, an environmental factor, is the medium of nutritional support to muscle cells, having significant impact on sarcopenia. Consequently, a significant amount of studies explored and showed the presence of gut microbiome-muscle axis (gut-muscle axis for short) which was possibly considered as the disease interventional target of age-related sarcopenia. However, the mechanism involved in the effect of gut- muscle axis on skeletal muscle health balance is mediated by various nutrients and are diverse. Therefore, it is necessary to study the mechanism of the gut-muscle axis, which the nutrients play a role on the therapeutic effect on the age-related sarcopenia through. This review summarizes the available literature on mechanisms and specific pathways of gut-muscle axis, and discusses the potential role and therapeutic feasibility of gut microbiota in age-related sarcopenia to understand the development of age-related sarcopenia and figure out the novel perspective of the potential therapeutic interventional targets.